Les systèmes graphiques de l’occitan - Hervé Lieutard (Lengas)
The graphic codes used to write Occitan have been the subject of occasional studies, but have never so far been the guiding thread for studying the history of the language in all its extent, perhaps because of the compartmentalization that exists and persists today between medieval philologists on the one hand and linguists and dialectologists on the other, who often give the impression of working on two distinct objects, where there is only one and the same language. The original graphic development that characterized Occitan in the Middle Ages and its spectacular decay in the sixteenth century are two facets of the same history, that of the Occitan language subject to constantly changing social and political constraints, both internal and external. In this paper, I will zoom in on some important points concerning the graphic history of Occitan to show that the study of graphic systems can be coupled with a sociolinguistic analysis that allows us to draw a social history of the language. At all times in this history, the graphic choices made collectively or individually reflect the greater or lesser prestige that the Occitan language occupies in French society or the representations associated with it.